PRODUCTION OF CANDIED VEGETABLE MARROW. INDUSTRIAL RAW MATERIAL. TECHNICAL CONDITIONS. NEW OBJECT FOR STANDARDIZATION - L.V. Pavlov; I.U. Kondratieva; O.T. Paraskova; V.V. Korinets; T.A. Sannikova; V.A. Machulkina (Овощи России, 2011)
On the base of research results on quality characteristics of candied vegetable marrow, for the first time the standard CTO 45727225-20 has been elaborated to control the quality of vegetable production and to improve the technological discipline in production of candied vegetable marrow.